Reduction of technological risks in subway and rail transport - Mel’nick, Viktorij; Karachun, Volodimir; Shybetskуу Vladislav; Fesenko, Sergii; Shafarenko, Nikolai (Technology audit and production reserves, 2017)
The aim of research is ensuring the guaranteed safety of passengers traveling on subway trains. The object of the researches carried out by the authors is process of interaction of the subway arriving at high speed to the subway station with the passenger, motionlessly waiting, or, which moves to the edge of the platform as a result of the braking of a close mass of passengers. It is shown that a significant friction of the heel surface of the passenger’s shoes and the friction of the upper body in the side surface of the car limits the possibility of human movement in space. Thus, in the simplest case, the upper part and extremities of the legs will form a fixed axis of rotation. But, a powerful blow deforms this axis and directs in such way that it will move over the surface, which is a collection of instantly rotational movements. And, thus, the instantaneous axis of rotation describes a conical surface with a vertex that coincides with the heels of the shoe. It is revealed that by rigidly tying the coordinate system xyz to a person it is possible to determine three Euler rotation angles relative to the instantaneous axis and to construct a table of directing cosines that allow determining the kinematic characteristics of the human forced body relative to the axes associated with it – ωxωyωz. The results of the model studies confirm the opinion about the expediency of replacing the translational motion of the side surface of the car with a complex movement, additionally equipped on the side surface of the car with a warning stripe. This stripe moves in the opposite direction to the car side, but with the same speed. Synthesis of these two movements gives the effect of the appearance of a fixed part of the warning stripe with respect to the passenger standing on the platform and, therefore, maximizes the confidence and reliability of the passengers’ transportation by electric trains of the subway. The laboratory model completely confirms the predicted effect of the danger absence of injury to passengers and the degree of technological risk presence in operating conditions.